Rekomendasi Badan Pengawas Pemilihan Umum Kepada Komisi Pemilihan Umum Dalam Menangani Pelanggaran Pemilu Pasca Penetapan Hasil Perolehan Suara Secara Nasional - Baljanan, Gilbert Marc; Lekipiouw, Sherlock Halmes; Pattinasarany, Yohanes (Jurnal Saniri, 2025)
Election administration violations, based on article 460 of the Election Law, Bawaslu has a maximum working time of 14 days to issue recommendations or decisions. Bawaslu's recommendations must be followed up by the KPU by issuing a decision letter no later than 3 days, as explained in Article 462. This problem occurs when the national vote results have been determined, then any dispute that occurs becomes the domain of the Constitutional Court. However, if a violation of election administration is found or reported, it must be followed up and decided by Bawaslu because it is based on article 454 paragraph 6 of the Election Law. The problem discussed by the author is Bawaslu's recommendation to be followed up by the KPU to change the determination of vote acquisition and the legal consequences that will be given if Bawaslu's recommendation is not followed up by the KPU.This writing uses a normative juridical research type, with a statutory regulation approach, a conceptual approach and a case approach.The research results show that regarding the legal force of Bawaslu's recommendation to change the vote tally, Bawaslu certainly has that legal force, because it is not legally prohibited. In connection with the follow-up to Bawaslu's recommendations to the KPU regarding violations of election administration, if the recommendations given by Bawaslu are not followed up by the KPU, they will be faced with various consequences, namely that the KPU can be reported by Bawaslu because it is related to the election organizer's code of ethics.